Fenologia de plantas e curva de maturação de frutos de caquizeiro - Nascimento, Lucas Marquezan (2020)
Climatic changes tend to cause changes in the phenological behavior of plants, directly influencing the development and changing the duration of the cycle. Such variations will influence the management, growth, seasonality of the plants and their fruits, as well as their maturation and quality. The objective was to evaluate the phenological behavior and fruit development of three common persimmon cultivars (Rama Forte, Giombo and Pomelo) conducted in the Midwest of Brazil. The plants were evaluated during four subsequent cycles, from August 2014 to June 2018. For the studies that involved the phenology of the plants, the following phenophases were counted, in days after the production pruning: swollen bud, green tip, sprouting , flowering, fruiting, fruits with 50% of the final size, fruits with 70% of the final size, fruits with 90% of the final size, beginning of the harvest and end of the harvest. For thermal sum the thermal sum or degrees-day (GD) was considered for the culture to complete each phenological phase. The number of accumulated cold hours (NHF) was also quantified. For the ripening curve, in 2018, 120 fruits were marked on six plants in the orchard. Weekly, two months after pruning and application of hydrogenated cyanamide (WAC), the transversal (DT) and longitudinal diameter of the fruit (DL) in the field were evaluated. From the 18th to the 31st week after the application of hydrogenated cyanamide, nine fruits were analyzed weekly being measured the color of the pulp and skin, external and pulp firmness (FIR), fresh mass, soluble solids content (SS), titratable acidity (AT), pH and Maturation Index. In hot years and with late pruning, plants sprouted more quickly. ‘Pomelo’ has adapted better to the local climate. The interval between sprouting and flowering in tropical conditions was shorter than that observed by other authors in milder climates. Annual climatic variations caused differences in the growth rates of the transverse diameter of the fruits. ‘Pomelo’, ‘Giombo’ and ‘Rama Forte’ reached the point of harvest with less thermal need compared to other published works. ‘Rama Forte’ and ‘Giombo’ did not show a pattern of thermal demand between the years. At least 400 hours below 14 ° C met the demand in cold hours of the persimmon tree. Fruit growth was faster until the 14th WAC. Between the 15th and the 20th WAC there was a reduction in the growth rate, and after the 22nd WAC the fruits started to have a more expressive growth. ‘Pomelo’ had bigger and heavier fruits. The epidermis of the fruits changed from green when immature to intense red when ripe. In three weeks, the external FIR went from 81 N to 5 N. The peak in the SS content of the fruits of ‘Pomelo’ and ‘Rama Forte’ was at the 26th WAC, and ‘Giombo’ at the 29th SAC. Under tropical savanna conditions, it is recommended that the best time to harvest the fruits of the cultivars is about three weeks before full maturity.